Condição periodontal e qualidade de vida em pacientes com doenças crônicas sistêmicas - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
Both Chronic Systemic Diseases (CSD) and Periodontal Disease (PD) can exhibit an additive and synergistic relationship and impact the individual's Quality of Life (QL). Both conditions can be catalogued as a stressor aggravating the individual's health condition, so that appropriate coping strategies and self-perception of both conditions become essential to improving health. The objective of this study was to analyze whether the periodontal condition interferes with the overall Quality of Life in patients with Chronic Systemic Diseases. The study included 252 individuals who were under medical follow-up for Chronic Systemic Diseases (CSD) at the Campos Gerais Regional University Hospital. In order to obtain the data, questionnaires(Self- Reported Periodontal Measure, SF-36 and Cope Breve) were applied in addition to the periodontal clinical examination. The results showed that the periodontal condition does not interfere with quality of life. The self-reported periodontal condition coincides with the periodontal clinical diagnosis, but individuals with worse periodontal condition had worse self- perception of their oral health. On the other hand, CSD interferes with QL, but it is not associated with or characterized as a risk factor for periodontitis. However, individuals with two or more CSD have better self-perception of oral health, but worse self-reported periodontal condition. Individuals with better Coping had worse self-perception of oral health. We concluded that the periodontal condition does not interfere with overall Quality of Life in individuals with Chronic Systemic Diseases. The self-reporting of the periodontal condition coincides with the clinical diagnosis of periodontal disease. Individuals with Chronic Systemic Diseases have good self-perception of oral health.
Keywords: Autorrelato; Doença Crônica; Qualidade de vida; Adaptação Psicológica; Self report; Chronic illness; Quality of life; Psychological adaptation; CNPQ::CIENCIAS DA SAUDE::ODONTOLOGIA